Methodology for designing technology for restoration of architectural monuments. Current state and prospects for development - Osipov, Sergei (Ways to Improve Construction Efficiency, 2023)
The article presents the results of the generalization of the past development of the methodology of designing technologies for the restoration of architectural monuments with an assessment of the current state and development prospects. For the first time, the author proposed the division of the past development of the methodology of designing the technology of restoration processes into four main periods, which collectively reflect the general history of the development of restoration as a construction business, compatible with the development of the main concepts and principles of restoration, namely: the first period - the development of the initial foundations of the methodology organizationally - technological design based on the generalization of original practical experience and theoretical principles of restoration of architectural monuments; the second period - the formation of modern foundations of the methodology of organizational and technological design of restoration technology, including its natural and scientific essence, topology and methods of decision-making, taking into account the accepted principles of restoration of architectural and historical monuments, decisions of the World Venice Congress of restorers; the third period - implementation and adjustment of the basics of information and analytical modeling of organizational and technological solutions regarding the design conditions of restoration of architectural and historical monuments; the fourth period - the formation of modern informational and numerical methods of organizational and technological design with the presentation of design results in the form of a multidimensional parametric image. It has been established that the selection of rational technological solutions for the implementation of restoration processes is carried out today, as well as the general technology of construction production - on the basis of the variability of the choice and multi-criteria technical and economic analysis. For the first time, the main reasons for the imperfection of the elements of the methodology of designing restoration technologies are established, which are due to its phenomenological immaturity and a significant amount of borrowings from the general technology of construction production regarding the main provisions of the theoretical foundations and logic of the theory.